Prolonged Endurance Exercise Adaptations Counteract Doxorubicin Chemotherapy-Induced Myotoxicity in Mice - Insu Kwon; Gwang-Woong Go; Youngil Lee; Jong-Hee Kim (Applied Sciences, 2022)
Doxorubicin (DOX) is a potent chemotherapeutic agent widely used for various types of cancer; however, its accumulation causes myotoxicity and muscle atrophy. Endurance exercise (EXE) has emerged as a vaccine against DOX-induced myotoxicity. However, potential molecular mechanisms of EXE-mediated myocyte protection for the unfavorable muscle phenotype remain unelucidated. In addition, most studies have identified the short-term effects of DOX and EXE interventions, but studies on the prolonged EXE effects used as adjuvant therapy for chronic DOX treatment are lacking. Twelve-week-old adult male C57BL/6J mice were assigned to four groups: sedentary treated with saline (SED-SAL, n = 10), endurance exercise treated saline (EXE-SAL, n = 10), sedentary treated with doxorubicin (SED-DOX, n = 10), and endurance exercise treated with doxorubicin (EXE-DOX, n = 10). Mice were intraperitoneally injected with DOX (5 mg/kg) or saline five times biweekly for eight weeks, while a treadmill running exercise was performed. Body composition was assessed and then soleus muscle tissues were excised for histological and biochemical assays. Our data showed that DOX aggravated body composition, absolute soleus muscle mass, and distinct pathological features; also, TOP2B upregulation was linked to DOX-induced myotoxicity. We also demonstrated that EXE-DOX promoted mitochondrial biogenesis (e.g., citrate synthase). However, no alterations in satellite cell activation and myogenesis factors in response to DOX and EXE interventions were observed. Instead, SED-DOX promoted catabolic signaling cascades (AKT-FOXO3α-MuRF-1 axis), whereas EXE-DOX reversed its catabolic phenomenon. Moreover, EXE-DOX stimulated basal autophagy. We showed that the EXE-mediated catabolic paradigm shift is likely to rescue impaired muscle integrity. Thus, our study suggests that EXE can be recommended as an adjuvant therapy to ameliorate DOX-induced myotoxicity.